Open-Loop Performance Analysis of Induction Motors under V/f Speed Control - jati, I Ketut Wirya; Nyoman Wahyu Satiawan, I (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2025)
This study aims to analyze the performance of a three-phase induction motor with a speed control system based on the Volt per Hertz (V/f) method in an open-loop configuration, with a primary focus on reducing torque drop during low-frequency operation. The simulation was carried out using MATLAB/Simulink, where the model consists of an SPWM-based three-phase inverter, a standard Simulink induction motor, and an external mechanical load. The V/f method was applied to maintain constant stator flux by keeping the voltage-to-frequency ratio fixed (approximately 7.6 V/Hz). The input frequency was varied from 10 Hz to 50 Hz, both under no-load and loaded conditions. The observed performance parameters included rotor speed, electromagnetic torque, stator current, and motor slip. The simulation results show that the system can produce a linear relationship between frequency and rotor speed with low slip (<5%) under no-load conditions. However, under load conditions, there is a speed drop of around 4–5% that cannot be compensated due to the absence of a feedback system. The initial electromagnetic torque demonstrates a fast response with an overshoot of up to 150 Nm before stabilizing in the range of 100–120 Nm. The rotor speed reaches a steady-state condition in approximately 0.2 seconds, indicating good dynamic response. In conclusion, the open-loop V/f control system is effective and sufficiently efficient for light industrial applications that do not require high precision, such as fans and pumps. However, for applications that demand greater stability and dynamic response, further development toward a closed-loop system or sensor-based adaptive control is recommended to enhance control accuracy, energy efficiency, and system capability in responding to dynamic loads